2015
DOI: 10.1016/j.medici.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Training strategy of explosive strength in young female volleyball players

Abstract: The 8-week combined jump and ball throwing training can significantly improve muscular performance in young female volleyball players. These findings may be useful for all physical education teachers and volleyball coaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
29

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 14 publications
5
62
0
29
Order By: Relevance
“…A direct comparison of findings of the study and of previous investigations is not possible due to differences in training models. But still, our results related to the increase of vertical jump performance confirm previous studies with different training models [23,39,45]. The results in the present study are parallel to those observed by Marques et al [40] who also found an increase of unloaded and loaded CMJ heights by varying percentages between 3.8 and 11.2% after 12-week of plyometric training in elite female volleyball players.…”
Section: Discussionsupporting
confidence: 92%
“…A direct comparison of findings of the study and of previous investigations is not possible due to differences in training models. But still, our results related to the increase of vertical jump performance confirm previous studies with different training models [23,39,45]. The results in the present study are parallel to those observed by Marques et al [40] who also found an increase of unloaded and loaded CMJ heights by varying percentages between 3.8 and 11.2% after 12-week of plyometric training in elite female volleyball players.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the study by Schwanke et al 12 when assessing abdominal strength in a sample of schoolchildren in Brazil, found results that point to strength gain. In this line of research, similar findings were found in studies by Chaves et al 3 Paul et al 19 Pereira et al 28 and Linhares et al…”
Section: Resultssupporting
confidence: 88%
“… %Δ, percent change from pre-test to post-test; BPT, balance training before plyometric training; BW, bodyweight; cm, centimeter; CMJ, counter movement jump; DJ, drop jump; Dom, dominant; Ex, exercises; FP, frontal plane; Freq, frequency; GCOM, combined resistance training and endurance; GR, resistance training alone; Int, intensity; IPT, plyometric training on unstable surface; Isok, isokinetic; Isom, isometric; kg, kilogram; m, meter; Mod, moderate; MVIC, maximal voluntary isometric contraction; N, number of participants; Nm, newton meter; NonDom, non-dominant; NPPT, no plyometric training; PBT, plyometric training before balance training; PE, physical education students; Pre, pre-test; PHV, peak height velocity; PL, plyometric; Post, post-test; Power, power measures; PPT, plyometric training; Reps, repetitions; RS, resisted sprinting; s, second; SD, standard deviation; SJ, squat jump; SP, sagittal plane; SPT, plyometric training on stable surface; SQ, squat; ST, Strength; Strength, strength measures; T, trained youth; Tr, training status; TRS, torso rotational strength; U, untrained youth; Wks, weeks . Additional Citations for Tables 2A,B are found in the text reference list (Hewett et al, 1996; Cossor et al, 1999; Witzke and Snow, 2000; Diallo et al, 2001; Matavulj et al, 2001; Martel et al, 2005; Szymanski et al, 2007; Meylan and Malatesta, 2009; Thomas et al, 2009; Buchheit et al, 2010; King and Cipriani, 2010; Skurvydas and Brazaitis, 2010; Skurvydas et al, 2010; Potdevin et al, 2011; Santos and Janeira, 2011; Lloyd et al, 2012; Noyes et al, 2012, 2013; Santos et al, 2012; Marques et al, 2013; Michailidis et al, 2013; Ramirez-Campillo et al, 2013, 2015a,b; Marta et al, 2014; Piazza et al, 2014; Sohnlein et al, 2014; Attene et al, 2015; Chelly et al, 2015; Pereira et al, 2015; Alves et al, 2016; Arabatzi, 2016; Borges et al, 2016; de Hoyo et al, 2016; Fernandez-Fernandez et al, 2016; Hall et al, 2016; McCormick et al, 2016; Moran et al, 2016; Rosas et al, 2016) .…”
Section: Resultsmentioning
confidence: 99%